Comparison of Two Acid Hydrotropes for Sustainable Fractionation of Birch Wood. Issue 17 (29th June 2020) - Cai, Cheng; Li, Jian; Hirth, Kolby; Huber, George W.; Lou, Hongming; Zhu, J. Y.
Abstract: This study reports on a comparative study of acid hydrotropic fractionation (AHF) of birch wood using maleic acid (MA) and p ‐toluenesulfonic acid ( p ‐TsOH). Under the same level of delignification, lignin dissolved by MA is much less condensed with a higher content of ether aryl β‐O‐4 linkages. Lignin depolymerization dominated in MA hydrotropic fractionation (MAHF) and resulted in a single lower molecular weight peak, in contrast to the competitive depolymerization and repolymerization in p ‐TsOH AHF with a bimodal distribution. The less condensed MA‐dissolved lignin facilitated catalytic conversion to monophenols. Carboxylation of residual lignin in fractionated cellulosic water‐insoluble solids (WISs) enhanced enzymatic saccharification by decreasing nonproductive cellulase binding to lignin. At a low cellulase loading of 10 FPU g −1 glucan, saccharification of WIS‐MT120 from MAHF at 120 °C was 95 % compared with 48 % for WIS‐PT85 from p ‐TsOH AHF at 85 °C under the same level of delignification of 63 %. Residual lignin carboxylation also facilitated nanofibrillation of WIS for producing lignin‐containing cellulose nanofibrils (LCNFs) through an enhanced lignin lubrication effect, which substantially decreases fibrillation energy. LCNFs from only one pass of microfluidization of WIS‐MT120 have the same morphology as those from WIS‐PT85 after three passes. MA also has a lower solubility and higher minimal hydrotropic concentration, which facilitated acid recovery. MA is U.S. Food and Drug Administration (FDA)‐approved as an indirect food additive, affording significant advantages compared with p ‐TsOH for biorefinery applications. Abstract : Acid hydrotropic fractionation : Maleic acid (MA) and p ‐toluenesulfonic acid are compared for sustainable wood fractionation at atmospheric pressure. Lignin esterification by MA facilitates fibrillating the fractionated water‐insoluble solids into cellulose nanofibrils, improving enzymatic hydrolysis of WIS by decreasing nonproductive binding of cellulase to lignin. MA dissolves 48 and 63 % lignin with 63 and 41 % β‐O‐4 linkages retained, respectively, and facilitates catalytic conversion to monophenols. MA also facilitates lignin precipitation and acid recovery.